Survival of probiotic lactic acid bacteria in the intestinal tract, their adhesion to epithelial cells and their ability to compete with pathogenic microorganisms - Botes, Marelize (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2008.